2011
DOI: 10.1111/j.1759-6831.2011.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of male flowers does not decrease with plant size in insect‐pollinated Sagittaria trifolia, contrary to predictions of size‐dependent sex allocation

Abstract: It has been proposed that relative allocation to female function increases with plant size in animalpollinated species. Previous investigations in several monoecious Sagittaria species seem to run contrary to the prediction of size-dependent sex allocation (SDS), throwing doubt on the generalization of SDS. Plant size, phenotypic gender, and flower production were measured in experimental populations of an aquatic, insect-pollinated herb Sagittaria trifolia (Alismataceae) under highly different densities. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 40 publications
0
22
2
Order By: Relevance
“…Thus, V. spinulosa shifted the balance between the two reproductive modes to adapt to different environments. Trade-offs in resource allocation between sexual and clonal reproduction have been demonstrated for aquatic species (Thompson and Eckert 2004, Reusch 2006, Van Drunen and Dorken 2012, whereas other studies failed to detect clear trade-off relationships (Eckert et al 2000, Han et al 2011. Based on the variability and trade-off of resource allocation between these two reproductive modes, we inferred that different populations of this species living in contrasting habitats are able to use different reproductive strategies.…”
Section: Evidence Of Trade-offs Between Sexual and Clonal Reproductionmentioning
confidence: 73%
See 1 more Smart Citation
“…Thus, V. spinulosa shifted the balance between the two reproductive modes to adapt to different environments. Trade-offs in resource allocation between sexual and clonal reproduction have been demonstrated for aquatic species (Thompson and Eckert 2004, Reusch 2006, Van Drunen and Dorken 2012, whereas other studies failed to detect clear trade-off relationships (Eckert et al 2000, Han et al 2011. Based on the variability and trade-off of resource allocation between these two reproductive modes, we inferred that different populations of this species living in contrasting habitats are able to use different reproductive strategies.…”
Section: Evidence Of Trade-offs Between Sexual and Clonal Reproductionmentioning
confidence: 73%
“…, Han et al. ). Based on the variability and trade‐off of resource allocation between these two reproductive modes, we inferred that different populations of this species living in contrasting habitats are able to use different reproductive strategies.…”
Section: Discussionmentioning
confidence: 99%
“…However, in a habitat with higher plant density or intense competition, many smaller corms would not develop into flowering individuals (Zhao, 2011). Other research also showed that S. trifolia can change its sex ratio and resource allocation modes in different individual densities (Han et al, 2011). Therefore, increasing resource allocation to big corms in a competitive environment might contribute to population maintenance in S. graminea.…”
Section: Discussionmentioning
confidence: 97%
“…Several previous studies have shown that the trade‐offs lead to varied conclusions in conditions with different nutrient levels or environmental conditions. For example, several studies detected a negative trade‐off relationship between reproductive modes (Snow & Whigham, ; Thompson & Eckert, ; Stark et al, ; Thiele et al, ; Van Drunen & Dorken, ), whereas others did not find a clear trade‐off relationship (Cain & Damman, ; Mendoza & Franco, ; Liu et al, ; Thiele et al, ; Han et al, ). The current study revealed that in low nutrient (control) or nutrient‐abundant (add‐N + P) conditions, there are no trade‐off relationships between S. graminea aboveground and belowground reproductive components.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation